The Effectiveness of Therapeutic Community on Increasing Hope Level of the Addicted Clients of These Centres - Aazam Shahmohammadi; Gholamreza Kheyrabadi (Drug Control Headquarters, Research and Education Office, 2011)
Introduction: The aim of this study was to determine the effectiveness of therapeutic community on the increasing hope level of the addicted clients of these centres. Method: This study is a semi experimental and was implemented in three stages of pre-test, post-test and follow-up: before offering the treatment program, after treatment and two months after treatment. Statistical society included all clients of the therapeutic centre in Isfahan during 1386. All 30 clients were asked to fill in the Snyder's adult hope scale questionnaire. Data were analyzed by the SPSS software and statistical methodology of variance analysis with repeated measurements. Findings: The results indicate that therapeutic community is effective on level of general hope scale of the clients. The results of the comparisons increased the therapeutic effectiveness on level of general hope scale of clients and show its effect on follow-up stage. Regarding the factor, therapeutic community has not had an increase and the follow-up stage has not been continuous during one month. Conclusion: Regarding the findings of this study, it is concluded that therapeutic community has been effective in increasing the hope level in general scale and can be used as a prevention factor.